Lost man's lane : a novel - Carson, Scott, 1982- (Emily Bestler Books / Atria, 2024)
For a sixteen-year-old, a summer internship working for a private investigator seems like a dream come true--particularly since the PI is investigating the most shocking crime to hit Bloomington, Indiana, in decades. A local woman has vanished, and the last time anyone saw her, she was in the backseat of a police car driven by a man impersonating an officer. Marshall Miller's internship puts him at the center of the action, a position he relishes until a terrifying moment that turns public praise for his sharp observations and uncanny memory into accusations of lying and imperiling the case. His detective mentor withdraws, friends and family worry and whisper, and Marshall alone understands that the darkness visiting his town this summer goes far beyond a single crime. Now his task is to explain it--and himself. --